Pengembangan Kacang Hijau Organik Sebagai Komoditas Pangan Indonesia - Riska Sekar Fitriani; Taryono Taryono (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2021)
Mungbean (Vigna radiata L.) is an important legume crops in Indonesia, because it can support food diversity, eventhough the production is lower than the demand. Mungbean can be used for different purposes such as vegetables and meals, therefore good agricultural practices in this case organic farming must be introduced, Organic farming practice by the application of organic mulch can improve the mungbean growth. The use of organic fertilizer which is one of important input in organic farming can increase the mungbean productivity. National mungbean production can be increased by the application of organic fertilizer and the introduction of organic farming in mungbean cultivation can produce more healthy nutritious food materials.